The clausal postmodification of a noun phrase in the written and spoken language - Bělohubá, Edita (Univerzita Pardubice, 2010)
The aim of this thesis is to focus on the occurrence of various types of the clausal postmodification of a noun phrase in spoken and written English. The theoretical part closely defines a noun phrase with the focus on its syntactic functions and then classifies its clausal postmodification on the basis of the finite and non-finite forms and also whether they have relative or appositive function. In the practical part of the thesis the author will investigate the occurrence of linguistic phenomena discussed in the theoretical part. It will be based on the analysis of authentic spoken and written English. The work will compare the frequency of individual clausal postmodifiers as well as their qualitative features. The focus will be also laid on the possible substitution of the various types. Eventually, the syntactic functions of head nouns will be discussed in terms of the postmodification that follows.
Větné postmodifikace podstatného jména v psaném a mluveném projevu
Keywords: větná skladba; postmodifikace; přístavek; vztažné věty; fráze; sentence structure; postmodification; apposition; phrase; relative clauses